1997
DOI: 10.1046/j.1471-4159.1997.68051804.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Tissue‐Specific Human Glutamate Dehydrogenase that Is Thermolabile and Highly Regulated by ADP

Abstract: Glutamate dehydrogenase (GDH), an enzyme that is central to the metabolism of glutamate, is present at high levels in the mammalian brain. Studies on human leukocytes and rat brain suggested the presence of two GDH activities differing in thermal stability and allosteric regulation, but molecular biological investigations led to the cloning of two human GDH-specific genes encoding highly homologous polypeptides. The first gene, designated GLUD1, is expressed in all tissues (housekeeping GDH), whereas the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
83
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 37 publications
6
83
1
1
Order By: Relevance
“…Taken together with the differences in their amino acid sequences and in their regulatory properties Shashidharan et al, 1997), the present findings support the possibility that different types of GDHs may function differently in a biological system, as many proteins have functions distinct from those for which they were originally identified. Actually, other roles of GDHs have been reported.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Taken together with the differences in their amino acid sequences and in their regulatory properties Shashidharan et al, 1997), the present findings support the possibility that different types of GDHs may function differently in a biological system, as many proteins have functions distinct from those for which they were originally identified. Actually, other roles of GDHs have been reported.…”
Section: Discussionsupporting
confidence: 74%
“…Our work also led to the finding that GDH is present in bovine brain in "heatlabile" (GDH I) and "heat-stable'' (GDH 11) forms . It has been reported that the activities of the GDH isotypes differ in their relative resistance to thermal inactivation, detergent extractability, and allosteric regulation characteristics (Colon et al, 1986;Shashidharan et al, 1997). Similar results were reported by other investigators showing that reduction in GDH activity in patients with neurodegenerative disorders was largely limited to the heat-labile form (Plaitakis et al, 1984).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Its function is to catalyse reversible deamination of glutamate into α-ketoglutarate and ammonium ion [2] [3] [4]. There are two forms: thermostable and thermolabile [1] [5] [6]. With thermal inactivation of serum, GLDH was found that almost one third of GLDH serum originated from the rough endoplasmic reticulum and the rest from mitochondria [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the activity of GDH is also enriched in the nuclear fraction as well as in the mitochondria fraction (Lai et al, 1986). Recent biochemical works led to the finding that multiple forms of GDH are present in mammalian system and that the activities of the GDH isotypes differ in their relative resistance to thermal inactivation, detergent extractability, and allosteric regulation characteristics (Plaitakis et al, 1984;2000;Abe et al, 1992;Shashidharan et al, 1997). These forms have been designated soluble and particulate GDH (Plaitakis et al, 1984;Colon et al, 1986;Hussain et al, 1989).…”
Section: Introductionmentioning
confidence: 99%